1986
DOI: 10.1116/1.583508
|View full text |Cite
|
Sign up to set email alerts
|

The role of gas phase reactions, electron impact, and collisional energy transfer processes relevant to plasma etching of polysilicon with H2 and Cl2

Abstract: Plasma etching of silicon with H2 and Cl2 was simulated with mixtures of H2, Cl2, and SiCl4. The gas phase chemistry was elucidated by varying power and pressure. The cross sections for production of H (3p2P) atoms were probed through the emission response to pressure variations. Addition of rare gases to a hydrogen plasma identified qualitatively major energy transfer paths between the rare gas metastables and the H2/H system. We conclude that dissociation of hydrogen molecules and excitation of hydrogen atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It has been found that the purge gas mixed with little chlorine gas is much more effective than pure ones [11,12]. Although hydrogen can be removed from aluminum melts by such techniques, the understanding of hydrogen solubility and diffusion is far from enough [13], and mechanism that chlorine gas used in degassing for complete hydrogen removal is still on considerable debate [12].…”
Section: Ab Initio MD Study On Mechanism Of Chlorine In Refiningmentioning
confidence: 99%
“…It has been found that the purge gas mixed with little chlorine gas is much more effective than pure ones [11,12]. Although hydrogen can be removed from aluminum melts by such techniques, the understanding of hydrogen solubility and diffusion is far from enough [13], and mechanism that chlorine gas used in degassing for complete hydrogen removal is still on considerable debate [12].…”
Section: Ab Initio MD Study On Mechanism Of Chlorine In Refiningmentioning
confidence: 99%
“…It is reasonable to neglect the two-step excitation process for the excitation of Ar (4p) via metastable Ar (4s) [19]. The predictive cascades and contribution of metastable H (2s) atoms to the production of H (n = 3) are both negligible.…”
Section: Kinetic Reactionsmentioning
confidence: 99%
“…Plasma surface reaction, which enables controllable heat generation, is one of the approaches for triggering grain coalescence and controlling the coalescence performance [1416]. Specifically, numerous plasma etching systems exhibit localized heat generation in the area of plasma/surface interaction [1722]. The plasmochemical reactions in these plasma etching systems are exothermic and able to thermally stimulate a wide range of physical processes and chemical reactions [21, 22].…”
Section: Introductionmentioning
confidence: 99%